2021
DOI: 10.1021/acs.orglett.1c00664
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light-Induced Cascade Cyclization of 3-Aminoindazoles, Ynals, and Chalcogens: Access to Chalcogen-Containing Pyrimido[1,2-b]-indazoles

Abstract: A direct cascade cyclization of 3-aminoindazoles, ynals, and accessible chalcogens facilitated by visible light has been developed. A series of fluoroactive selenium/tellurium-substituted pyrimido­[1,2-b]-indazoles were easily accessed in moderate to good yields with a broad scope. Furthermore, we surveyed the spectral properties of selenide pyrimido­[1,2-b]-indazoles prepared by this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…On the basis of the above experimental outcome and literature reports, we have proposed a plausible mechanistic path of this heteroaryl silylation of olefins as illustrated in Scheme . Initially, a single-electron transfer (SET) occurs from iron­(II) to the excited state of EY (EY*) and generates photocatalyst radical anion EY •– and iron­(III) .…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…On the basis of the above experimental outcome and literature reports, we have proposed a plausible mechanistic path of this heteroaryl silylation of olefins as illustrated in Scheme . Initially, a single-electron transfer (SET) occurs from iron­(II) to the excited state of EY (EY*) and generates photocatalyst radical anion EY •– and iron­(III) .…”
mentioning
confidence: 81%
“…Recently, visible-light photocatalysis has become an impressive tool in organic synthesis . In this realm, the merger of transition-metal catalysis and visible-light photoredox catalysis offers an exciting opportunity to perform the organic transformations under mild conditions. , In continuation of our efforts in the field of visible-light-mediated functionalization of imidazopyridine, herein we report a three-component carbosilylation of alkenes with imidazoheterocycles and silanes by merging visible-light photocatalysis and iron­(II) catalysis (Scheme ).…”
mentioning
confidence: 99%
“…We have long been committed to developing new methods to construct nitrogen-containing heterocyclic derivatives. [69][70][71][72][73] Thus, easily available 2-phenylindolizine and diphenylcyclopropenone were chose as the model substrates to conduct the reaction under 120 o C in DCM for 18 h (Table 1). Surprisingly, the sequence deconstructive recycloaromatization product was secured with a prominent yield (95%) without any catalysts and additives (Table 1, entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent work, Zhou et al reported the use of diselenides and digermanides in the preparation of pyrimido[1,2-b]indazoles. 186 Organoselenium compounds are attracting great interest in the pharmaceutical field, and novel approaches for the introduction of selenium atoms are being investigated. Conventional methods involve the electrophilic difunctionalization of unsaturated bonds and require the use of oxidants together with activation by either acid or Lewis bases.…”
Section: Scheme 89mentioning
confidence: 99%